Research on fault self-healing strategy of a distribution network considering wind and solar accommodation capacity - Jiang, Lin; Wang, Canbin; Li, Chen; Xiang, Caili (Frontiers in Energy Research, 2025)
As a traditional fault recovery strategy, network reconfiguration changes the structure of a distribution network by changing the switching state to achieve a normal power supply for non-fault power loss. Distributed access, such as wind power and photovoltaics, will cause voltage and frequency fluctuations. Traditional tie switches cannot adapt to this change, which may lead to reconstruction failure. A flexible interconnection device can suppress the negative impact of these large-scale sources and loads with strong uncertainty and volatility on the power supply quality and system stability. This paper proposes a fault recovery strategy for a distribution network considering wind and solar consumption. First, through the analysis of the fault recovery process of a distribution network, it is proposed that the fault recovery of a distribution network can be realized by distribution network reconfiguration. Then, by analyzing the characteristics of the flexible interconnection device, it is shown that the flexible interconnection device can adapt well to the distribution network with new energy access. Finally, this paper constructs a multi-objective optimization reconfiguration model of a distribution network considering wind and solar consumption capacity and verifies the effectiveness of the scheme in improving wind and solar consumption capacity and solving economic problems through case analysis.